(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Purpose: The purpose of this study is to assess digital eye strain (DES) with the help of the digital eye strain scoring index (DESSI) in the urban population. Methods: The subjects were carefully selected with no ocular or systemic problems that may alter the study results and prior written consent was obtained. This study is divided into two phases. Phase 1 consists of reliability testing with Cronbach’s alpha and test-retest reliability while phase 2 consists of validity testing with internal validity, sensitivity and specificity. In phase 1 there were two visits, a baseline visit and a retest visit with 24 hours gap. DESSI was implemented on both visits. Phase 2 had two visits on the same day called the pre-task visit and post-task visit separated by one-hour task performance. Pre and post-task assessments were compared for all variables in the DESSI. The smartphone addiction scale (SAS) assessment and disability index (DI) was correlated with the no. of hours of smartphone use. The sensitivity and specificity were also assessed. Results: In phase 1, Cronbach’s alpha value was 0.82 and the co-relation coefficient was found to be acceptable to excellent whereas, in phase 2, the paired sample t-test showed statistically significant differences for all the tests compared. The SAS and DI correlation with the no. of hours of smartphone use was found to be good. The sensitivity and specificity of DESSI were fair, scoring 51% and 53% respectively. Conclusion: The digital eye strain is a useful tool for clinicians who can accurately analyze digital eye strain with acceptable to excellent test–retest reliability, internal consistency, good validity, fair sensitivity, and specificity.